Nest, readapting a domestic landscape - Costa, Carlos Casimiro da (2014)
Abstract do Paper “Nest - Readapting a Domestic Landscape” Paper distinguido como um dos 30 melhores para comunicação pelo júri da comissão científica da 16th International Conference - Sustainable Innovation 2011 - Towards Sustainable Product Design, Centre for Sustainable Design, Farnham Castle, United Kingdom, comissariado por Martin Charter.